2005
DOI: 10.1021/ja051079g
|View full text |Cite
|
Sign up to set email alerts
|

Using Liquid Crystals to Report Membrane Proteins Captured by Affinity Microcontact Printing from Cell Lysates and Membrane Extracts

Abstract: The chemical heterogeneity of proteins makes development of general and facile surface-based methods for protein analysis a substantial challenge, particularly when analyzing transmembrane proteins. Here, we report a simple surface-based procedure that permits detection of transmembrane proteins from crude cell lysates and cell membrane extracts. The method relies on the use of thermotropic liquid crystals to amplify and report the presence of the transmembrane proteins captured by an affinity ligand on the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…The orientational properties of liquid crystals (LCs) enables the amplification and the transduction of biologically relevant binding events at nanostructured surfaces into optical outputs. [1][2][3] They can be used to image receptor-mediated binding of proteins at surfaces with submicrometer spatial resolution. 4,5 This method is potentially useful because it does not require the use of enzymatic or fluorescent labels, which largely complicate surface-based assays and prevent high levels of multiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…The orientational properties of liquid crystals (LCs) enables the amplification and the transduction of biologically relevant binding events at nanostructured surfaces into optical outputs. [1][2][3] They can be used to image receptor-mediated binding of proteins at surfaces with submicrometer spatial resolution. 4,5 This method is potentially useful because it does not require the use of enzymatic or fluorescent labels, which largely complicate surface-based assays and prevent high levels of multiplexing.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14] What makes LCs useful mainly stems from its optical anisotropy properties such as optical birefringence, which arises from the different refractive indices along two molecular axes of LCs, ie, n o and n e along the ordinary and the extraordinary axes, respectively. The orientations of LCs dominate changes in optical birefringence of LCs, and its control forms a basis of electro-optical switching and LC-based optical biosensors.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] One of the most important advantages of LCs-based sensors is that the orientational properties of LCs enable the sensitive amplification and transduction of a series of interactions into optical outputs that are visible to the naked eye between crossed polarizers due to the birefringence of LCs. [7][8][9] When compared with traditional analytical methods, LCs based sensors have many advantages including that they do not require labeling of substrates, complex instrumentations, or tedious sequences of actions. 4,5 Previous studies have shown that the orientational transition of LCs could be coupled to a range of biomolecular interactions such as specific-binding events and enzyme activities at planar interfaces between LCs and the aqueous phases.…”
Section: Introductionmentioning
confidence: 99%